What Can Countries in Other Regions Learn from Social Security Reform in Latin America? - Gill, Indermit S.; Ozer, Ceren; Tatucu, Radu (World Bank, 2012)
About a dozen countries in Latin America have enacted reforms that include elements being contemplated elsewhere, including the partial privatization of social security. It is not easy to draw universal lessons for social security reform from the experience of countries such as Argentina, Chile, and Mexico, however, where sizeable public pension systems went bankrupt before the populations aged, mainly because of mismanagement. Most developing economies have much smaller social security systems. Relatively well-managed systems in industrial countries face problems that are long term in nature and have been brought about by an aging population. The experiences of Latin America nevertheless offer some general lessons for countries in other parts of the world. These lessons relate to changes in labor market incentives accompanying reforms and how workers react to them, government actions that have met with success in managing the transition to funded pensions, and the expectations of individuals from social security systems. Latin America's reforms suggest that the most effective approach is to keep payroll taxes low, governments solvent, and social security systems focused on providing reasonable insurance against poverty in old age.